Modelling and development of carbon molecular sieve membrane for gas separation - Su, Jincai (2008)
The objective of the research project was to investigate the feasibility of preparing carbon molecular sieve membranes from Kapton® polyimide film. The effects of carbonisation parameters on the gas transport properties of the carbon membranes were studied using statistical analysis. Carbonisation temperature had the strongest influence on gas permeation through the carbon membranes. Both the carbonisation atmosphere and the thermal soak time had limited effects on the pore size of the carbon membranes. The heating rate did not have any influence on the development of the membrane structure during the carbonisation process.